Assessment of sdLDL-C by Three Different Formula and Its Correlation with Clinical Variables Among Diabetes Individuals with and without Nephropathy - Desy Thayyil Menambath; Durga Rao Yella; Ashok Prabhu Khandige; Sudha Kuthethur; Nandini Mangalore (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Diabetes mellitus is a common disease worldwide which affects renal function. Cardiovascular morbidity and mortality in diabetes patients can be accelerated by dyslipidemia. Small dense lowdensity lipoprotein-cholesterol (sdLDL-C) is atherogenic and its predominance has been known as a cardiovascular risk factor. The study aimed to assess the validity of calculated sdLDL-C using three different formulae and its association with other clinical variables in diabetic patients with and without nephropathy, and also to determine the best suited formula to measure sdLDL-C.METHODS: The study subjects were divided into two groups based on the amount of albumin excreted in the urine. Group I or the control group consisted of diabetic subjects without microalbuminuria, while group II consisted of diabetic subjects with microalbuminuria. Blood glucose, glycated haemoglobin (HbA1c), creatinine, total cholesterol (TC), triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C), LDL-C and apoB were estimated. Three formulae used for the validation of calculated sdLDL-C were TG/HDL, sdLDL (mg/dL) = 0.580 (nonHDL) + 0.407 (direct-LDL-C) – 0.719 (calculated-LDL-C) – 12.05, and LDL-C/LDL apoB.RESULTS: There was no significant difference in sdLDL-C levels of diabetic subjects with and without nephropathy. The sdLDL-C had strong correlation with TC, TG, LDL-C, very-low-density lipoprotein (VLDL), non-HDL and apoB in both study groups. ROC curve showed that LDL-C/LDL apoB derived sdLDL-C had better sensitivity (85%) and specificity (69%) compared to other two measures.CONCLUSION: Though the calculated sdLDL-C do not predict the occurrence of nephropathy in diabetes subjects, it may still be used in conjunction with the traditional markers since it is cost effective. The LDL-C/LDL apoB formula is the best predictor of sdLDL-C among the three equations.KEYWORDS: HDL-C, LDL-C, Microalbuminuria, sdLDL-C, T2DM